1997
DOI: 10.1359/jbmr.1997.12.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Vitamin D Receptor Gene Alleles on Bone Mineral Density in Postmenopausal and Osteoporotic Women

Abstract: It is well established that genetic factors contribute to bone turnover and bone density. Evidence exists suggesting that a major part of this genetic influence may be due to polymorphisms in the vitamin D receptor (VDR) gene. However, it is not clear whether the VDR genotype effect persists in elderly women. In the present study, the relationship between the BsmI, ApaI, and TaqI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 23 publications
5
63
1
1
Order By: Relevance
“…Postmenopausal osteoporosis is a common disease associated with aging, mainly in postmenopausal eldly women, which seriously affect their health and quality of life, and even shorten life expectancy [12][13][14]. Gross et al [15] conducted a study in postmenopausal Mexican-American women, showed that FokI polymorphism of the VDR gene correlates significantly with decreased BMD at the lumbar spine and an increased rate of bone loss at the hip in ff subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Postmenopausal osteoporosis is a common disease associated with aging, mainly in postmenopausal eldly women, which seriously affect their health and quality of life, and even shorten life expectancy [12][13][14]. Gross et al [15] conducted a study in postmenopausal Mexican-American women, showed that FokI polymorphism of the VDR gene correlates significantly with decreased BMD at the lumbar spine and an increased rate of bone loss at the hip in ff subjects.…”
Section: Introductionmentioning
confidence: 99%
“…According to our inclusion criteria, a total of 11 eligible studies involving 1468 cases and 2177 controls were included in the pooled analysis (Berg et al, 1996;Vandevyver et al, 1997;Gomez et al, 1999;Valimaki et al, 2001;Zajickova et al, 2002;Douroudis et al, 2003;Zhu et al, 2004;Garnero et al, 2005;Horst-Sikorska et al, 2005;Mitra et al, 2006;Ge et al, 2009). The characteristics of selected studies are summarized in Figure 1.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…Several studies in Caucasian and Asian populations (Yamagata et al 1994;Fleet et al 1995;Koshiyama et al 1995;Riggs et al 1995;Gross et al 1996;Momson et al 1997;Tamai et al 1997) have shown an allelic effect between extreme homozygotes of perhaps 0.5 SD units, with a difference in bone density ranging from 4 to 13 %. Other studies have reported little or no effect in various Caucasian populations (Hustmyer et Barger-Lux et al 1995a, b;Garnero et al 1995;Keen et al 1995;Kroger et al 1995;Jorgensen et al 1996;Alahari et al 1997;Francis et al 1997;Gunnes et al 1997;McClure et al 1997;Vandevyver et al 1997). Moreover, three studies, including a large Dutch study, have reported a VDR gene allele effect but in the opposite direction to that of the previous studies (Houston et al 1996;Uitterlinden et al 1996;Salamone et al 1996).…”
mentioning
confidence: 95%
“…Also, VDR genotype has been related to body size at various stages of life from infancy onwards (BargerLux et al 1995a, b;Keen et al 1997;Tamai et al 1997). Furthermore, in one study of femoral-neck bone density a VDR allele effect was noted in average-weight subjects but not in obese subjects (BMI >30kg/m2;Vandevyver et al 1997). These interactions with body and bone size will need to be carefully elucidated before the potential for interaction between genetic factors and nutritional intake can be fully understood.…”
mentioning
confidence: 99%